(untitled) (Communications in Computational Physics, 2007)
Outflow boundary conditions (OBCs) are investigated for calculation of incompressible flows by spectral element methods. Several OBCs, including essential-type, natural-type, periodic-type and advection-type, are compared by carrying out a series of numerical experiments. Especially, a simplified form of the so-called Orlanski's OBCs is proposed in the context of spectral element methods, for which a new treatment technique is used. The purpose of this paper is to find stable low-reflective OBCs, suitable and flexible for use of spectral element methods in simulation of incompressible flows in complex geometries. The computation is firstly carried out for a 2D simulation of Poiseuille-Bénard channel flow with Re=10, Ri=150 and Pr=2/3. This flow serves as a useful example to demonstrate the applicability of the proposed OBCs because it exhibits a feature of vortex shedding propagating through the outflow boundary. Then a 3D flow around an obstacle is computed to show the efficiency in the case of more general geometries. Among the tested OBCs, the advection-type OBCs are proven to have better behavior as compared with the others.